1970
DOI: 10.1177/003693307001500702
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Function in Pregnancy

Abstract: In this investigation 60 pregnant patients underwent serial estimation of forced vital capacity (FVC) and forced expiratory volume (FEV1) throughout pregnancy and after delivery. No significant change occurred in the group mean figures of these measurements of ventilatory function. When patients were divided into those who were non-smokers and those who smoked more than 10 cigarettes daily it appeared that both FVC and FEV1 during the last 8 weeks of pregnancy were slightly reduced in the smokers. Previous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1974
1974
2004
2004

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…With some minor exceptions, most studies have tended to confirm this pattern of change (l, [33][34][35][36][37][38][39][40][41][42]. In particular, there is a consistent decrease in ERV late in pregnancy, with values ranging from 8 to 40 070 less than nonpregnant control values.…”
Section: Lung Volumesmentioning
confidence: 99%
See 1 more Smart Citation
“…With some minor exceptions, most studies have tended to confirm this pattern of change (l, [33][34][35][36][37][38][39][40][41][42]. In particular, there is a consistent decrease in ERV late in pregnancy, with values ranging from 8 to 40 070 less than nonpregnant control values.…”
Section: Lung Volumesmentioning
confidence: 99%
“…The numerous studies that have examined flows throughout the course of pregnancy have consistently demonstrated no alterations in the forced expiratory volume in 1 s (FEV,) or the ratio of FEV\ to the forced vital capacity (FVC) (33)(34)(35)(36)(41)(42)(43), suggesting that large airway function is not impaired during pregnancy. In an early study of total pulmonary resistance in pregnancy, Rubin and co-workers (42) presented data supporting a decreased total pulmonary resistance in late pregnancy.…”
Section: Airway Function and Mechanicsmentioning
confidence: 99%
“…Cameron, Bain and Grant, 1970;Sims, Chamberlain and de Swiet, 1976;Milne et al, 1977c). However, there is disagreement as to what happens to airways resistance (Raw) measured during quiet respiration.…”
Section: Large Airways Functionmentioning
confidence: 99%
“…fibrinogen and imniiinoglobulins, notably IgE. T h e nomenclature used for the description of light microscopic findings was principally in accordance with that of Canieron ( 6 ) . A variety of kidney ailments, including transplants, were studied.…”
mentioning
confidence: 99%